Public private partnership monitor. (Metro Manila, Philippines Asian Development Bank, 2019)
The countries covered include Bangladesh, Georgia, India, Indonesia, Kazakhstan, Pakistan, Papua New Guinea, the People Republic of China, the Philippines, Sri Lanka, Thailand, and Viet Nam. About 200 quantitative and qualitative indicators were assessed, divided into four main categories: Regulatory Framework, Institutional Capacity for Implementation, PPP Market Maturity, and Financial Facilities. The Public Private Partnership Monitor aims to act as a policy tool to create a dialogue between the public and private sectors, and provide an enabling environment for PPPs.
Keywords: Public administration -- Developing countries; Economic development -- Social aspects; Electronic books